Correspondência remetida por eminentes pré-historiadores europeus a José Leite de Vasconcelos (1853-1941) - Cardoso, João Luís (2018)
The correspondence received by J. Leite de Vasconcelos from thirteen archaeologists of Swedish, English, French, Italian, Swiss and German nationality, evidence the internationalization achieved by the Director of the Portuguese Ethnological Museum. The missives, almost all of them of the twentieth century, when the scientific prestige of Leite de Vasconcelos had reached the peak, deal with very different, generally relevant themes, sometimes resulting from visits made by the author himself to his correspondents, or, on the contrary, of visits made by them to Lisbon, thus enabling a direct knowledge. In fact, the mobility of Leite de Vasconcelos is well-known, which is in keeping with its declared love of traveling. These missives sometimes address scientific questions of first importance, contributing to the knowledge of the state of archaeological research in the respective countries, with international repercussions.